Flavonoid component determination and apoptotic induction evaluation of houttuynia cordata thunb extract on human acute leukemic cells - Boonyawee N,; Chaowanee W,; Paweena P,; Supantitra Chanprasert, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Development of resistance to currently used drugs and side effects of several allopathic drugs have led to increased emphasis on plant materials uses as a source of medicines for a wide variety of human illnesses including leukemia. Houttuynia cordata Thunb (H.cordata), a Northern Thailand local plant and commonly known as Plucao, has various biological activities such as anti-inflammatory, anti-cancer and anti-leukemic activities. We aimed to determine active flavonoid components of H.cordata and to investigate the effect of H.cordata ethanolic extract on apoptotic induction on human acute lymphoblastic leukemia cells. In this study, we found that H.cordata ethanolic extract had total flavonoid of 231.21 ± 4.19 mg QE/g dried H.cordata. The extract analyzed by quantitative LC-MS consists of several flavonoid components including hyperin 6.35 ± 0.41, quercetin 0.34 ± 0.02, isoquercetin 1.10 ± 0.03, and rutin 0.88 ± 0.04 (%w/w). The cytotoxicity results showed dose dependent decrease in growth of Jurkat leukemic cells. Blebbing pattern of cell apoptosis was found in cells treated with H.cordata ethanolic extract for 24 and 48 hrs. Moreover, we found that the extract could substantially induce Jurkat cell death through apoptosis at both 12 and 24 hrs. In conclusion, these results indicated that H.cordata ethanolic extract which is composed of several flavonoids, possesses anti-leukemic activity through apoptotic induction in Jurkat leukemia cells.